Herbarium Specimens: A Treasure for DNA Extraction, an Update - Záveská Drábková, Lenka (Methods in molecular biology, 2021)
With the expansion of molecular techniques, the historical collections have become widely used. The last boom started with using next- and second-generation sequencing in which massive parallel sequencing replaced targeted sequencing and third-generation technology involves single molecule technology. Studying plant DNA using these modern molecular techniques plays an important role in understanding evolutionary relationships, identification through DNA barcoding, conservation status, and many other aspects of plant biology. Enormous herbarium collections are an important source of material especially for taxonomic long-standing issues, specimens from areas difficult to access or from taxa that are now extinct. The ability to utilize these specimens greatly enhances the research. However, the process of extracting DNA from herbarium specimens is often fraught with difficulty related to such variables as plant chemistry, drying method of the specimen, and chemical treatment of the specimen. The result of these applications is often fragmented DNA. The reason new sequencing approaches have been so successful is that the template DNA needs to be fragmented for proper library building, and herbarium DNA is exactly that. Although many methods have been developed for extraction of DNA from herbarium specimens, the most frequently used are modified CTAB and DNeasy Plant Mini Kit protocols. Nine selected protocols in this chapter have been successfully used for high-quality DNA extraction from different kinds of plant herbarium tissues. These methods differ primarily with respect to their requirements for input material (from algae to vascular plants), type of the plant tissue (leaves with incrustations, sclerenchyma strands, mucilaginous tissues, needles, seeds), and further possible applications (PCR-based methods, microsatellites, AFLP or next-generation sequencing).
Keywords: Amplified Fragment Length Polymorphism Analysis; orgánová specificita; taxonomické DNA čárové kódování; DNA Barcoding, Taxonomic; chemická frakcionace; DNA, Plant; polymerázová řetězová reakce; listy rostlin; reagenční diagnostické soupravy; Polymerase Chain Reaction; High-Throughput Nucleotide Sequencing; analýza polymorfismu délky amplifikovaných restrikčních fragmentů; Plant Leaves; rostliny; vysoce účinné nukleotidové sekvenování; DNA rostlinná; Microsatellite Repeats; Sequence Analysis, DNA; Plants; Organ Specificity; sekvenční analýza DNA; Chemical Fractionation; mikrosatelitní repetice; Reagent Kits, Diagnostic